Occurrence of per- and polyfluoroalkyl substances (PFASs) in raw milk and feed from nine Chinese provinces and human exposure risk assessment. (August 2022) - Liu, Yifei; Zhang, Qinghua; Li, Yingming; Hao, Yanfen; Li, Jingguang; Zhang, Lei; Wang, Peilong; Yin, Yuhan; Zhang, Su; Li, Tong; Wang, Yaxin; Dong, Shujun; et al.
Abstract: The per- and polyfluoroalkyl substances (PFASs) are substantially produced and applied in industrial and domestic products, which have recently aroused great public concern for their potential toxicity to humans. In the present study, raw milk (n = 107) and cow feed samples (n = 70) were collected across nine Chinese provinces, in order to investigate the occurrence of PFASs in milk and feed, and the human exposure risk to milk. The concentrations of PFASs are in the range of < method detection limit −9.82 ng/g dw (average: 1.03 ng/g dw) for milk and 0.99–144 ng/g dw (7.68 ng/g dw) for feed. Perfluorobutanoic acid (34.0%) dominates in feed, while perfluorooctanesulfonic acid (67.5%) dominates in milk. No significant positive correlations of PFASs are observed between paired feed and milk ( p  > 0.05). However, feeds collected around fluorination production area show relatively higher PFAS levels than those from other areas, which also increase PFAS levels in milk. Risk assessment of PFASs through milk consumption is carried out according to evolving reference doses (RfDs). The hazard quotient is more than one for both adults and children when the strictest RfDs are applied. The Monte Carlo Simulation shows that children face higher PFAS exposure risk than adults. Graphical abstract: Image 1 Highlights: PFASs are ubiquitous in feed and milk, with 7.5-fold higher in feed than in milk. Fluorination production elevate PFAS levels in feed and milk. PFBA dominates in feed, while PFOS dominates in milk. Hazard quotients of PFASs are higher for children than adults.